A protocol for a Canadian prospective observational study of decision-making on active surveillance or surgery for low-risk papillary thyroid cancer. Issue 4 (12th April 2018) - Sawka, Anna M; Ghai, Sangeet; Tomlinson, George; Rotstein, Lorne; Gilbert, Ralph; Gullane, Patrick; Pasternak, Jesse; Brown, Dale; de Almeida, John; Irish, Jonathan; Chepeha, Douglas; Higgins, Kevin; et al.
Abstract : Introduction: Low-risk papillary thyroid cancer (PTC) is increasingly being diagnosed throughout the world; yet the mortality risk is low compared with other malignancies. Traditional management includes thyroid surgery, sometimes followed by radioactive iodine and thyroid hormone treatment. Active surveillance (AS) has been proposed as a means to reduce overtreatment of PTC. AS involves close disease follow-up, with the intention to intervene if the disease progresses, or on patient request. Methods and analysis: This is a multiphase prospective observational study. In the first phase of this study, consenting eligible adults with low-risk PTC, that is, <2 cm in maximal diameter, confined to the thyroid and not immediately adjacent to critical structures in the neck, are provided verbal and written information about PTC disease prognosis following surgery or AS. Questionnaires are administered at baseline and after the disease management decision on AS or surgery is finalised. Patients may choose either option (surgery or AS), and the primary outcome is the frequency with which either disease management option is chosen. Secondary outcomes include: rationale for the decision, role of the patient in decision-making and decision satisfaction. In the second phase of the study, consenting eligible adult patients who completed the first study phase may enrol in respective AS or surgery group follow-up studies. The following outcomes are examined 1 year after enrolment in the follow-up phase: decision regret about disease management choice (primary outcome), psychological distress, disease-specific quality of life, fear of disease progression, body image satisfaction, disease progression, crossover to surgery in the AS group, new chronic thyroid hormone use and healthcare resource utilisation. Ethics and dissemination: The University Health Network Research Ethics Board approved this study (ID 15-8942). The results will be published in an open access journal. Trial registration number: NCT03271892 ; Pre-results.